도시 가로시설물의 조형 요소와 선호도 간의 상관성 분석 - 강규범; Gui Bum Kang; 조세환; Se Hwan Cho (한국조경학회지, 2014)
본 연구는 가로 시설물 디자인의 조형 요소와 가로경관 선호도 간의 상관성 분석을 목적으로 수행되었으며, 일산 신도시의 가로 공간 내 입지하고 있는 휴식, 위생, 조명, 정보, 판매, 교통, 조경 관련 다양한 가로시설물을 연구 대상으로 하였다. 연구는 가로시설물 관련 문헌조사를 기반으로 이론을 고찰하고, 설문조사 및 분석을 통해 결과를 고찰하는 방법으로 진행하였으며, 다음과 같은 연구 결과를 얻을 수 있었다. 첫째, 가로경관에 영향을 미치는 요소를 파악하기 위한 분석에서 ‘휴식시설’과 ‘정보시설’, ‘조경시설’ 등 3개 요소가 가로경관에 주요 영향을 미치는 요소로 나타났다. 특히 이들은 ‘휴식’, ‘조경’, ‘정보’ 시설 순으로 경관 선호도에 큰 영향력을 미치고 있었으며, 휴식시설에는 각종 ‘의자 요소’가, 정보시설‘에는 ‘사인보드’가, 조경시설에는 ‘조형물’, ‘분수’, ‘문주’ 등의 시설 요소가 경관 선호도에 주된 영향을 미치는 요소인 것으로 분석되었다. 둘째, 형태, 색채, 질감, 스케일 등 조형요소가 가로시설물의 선호도에 미치는 영향을 분석한 결과, 휴식시설인 의자는 ‘질감’, ‘형태’, ‘스케일’, ‘색채’의 순으로 조형 디자인 요소가 경관 선호도에 영향을 미치는 것으로 나타났다. 특히 ‘색채’ 요소가 다른 3개 요소에 비해 상대적으로 경관 선호도에 적은 영향을 미치고 있는 것으로 통계적 유의성이 있는 것으로 나타났는데, 이것은 의자 등 편의시설에서는 질감, 형태, 스케일 등 기능적인 사항이 색채 등 시각적 것보다 선호도에 크게 영향을 미치고 있음을 시사하고 있는 것이었다. 조경시설 중 모뉴먼트와 관련된 시설은 경관 선호도에 있어 ‘색채’, ‘형태’, ‘질감’, ‘스케일’ 등의 순으로 영향을 미치고 있는 것으로 나타남으로써 의자 등 편의시설과는 다른 양상을 보이고 있는 것으로 나타났다. 이것은 색채, 형태 등 시각적 요소가 오히려 경관 선호도에 중요한 영향을 준다는 것을 의미하고 있는 것으로 사료되었다. 셋째, 특히, 사인보드 등 정보시설에 있어 경관 선호도와 디자인의 조형 요소와의 상관관계에 있어서는 부(否)의 상관성이 있는 것으로 나타났다. 즉, 사인보드가 경관 선호도에 매우 부정적 영향을 끼치는 것을 의미하고 있음인데, 디자인 조형요소와의 상관성은 ‘스케일’, ‘색채’, ‘질감’의 순으로 나타남으로써 ‘스케일’ 즉 광고물의 ‘크기’와 ‘색채’가 경관 선호도에 악영향을 미치고 있음을 의미하였다. 이상의 결과는 가로 경관 요소로서 가로 시설물을 디자인하고자 할 경우, 시설물의 종류에 따라서 상이한 조형 요소에 상대적으로 집중적 관심을 쏟아야 할 필요가 있음을 보여주고 있었다. 마지막으로, 가로시설물을 분류함에 있어서 지금까지 교과서적으로 분류해 온 ‘기능’ 중심의 ‘계’ 차원의 분류체계는 경관성과 관련하여서는 바람직하지 않은 것으로 나타났으며, 따라서 경관과 관련한 연구를 수행할 경우, ‘계’보다는 ‘시설 종류’ 차원으로 분류하는 것이 보다 바람직한 것으로 나타났다. This study was carried out for the purpose of analysis correlations between street furniture design elements and preference of street furniture. This research analyzed the various street furniture set on Ilsan new town street, which are rest, hygiene, light, information, sale, traffic, and landscape. This study has processed by analysing street furniture literature investigation and consideration of theory. First, for analysed effect of street furniture element, has been appear as element ‘relaxation facilities’, ‘information facilities’, landscape facilities` mainly effect on street. Specially, ‘rest’, ‘landscape’, ‘information’ in order had a major influence on scenery. Each kind of ‘chair elements’ in rest facilities, ‘sign board’ in information facilities, ‘sculpture’, ‘fountain’ in ‘landscape facilities’ has analyzed as the main elements in the landscape affinity property affecting factor. Second, the results of analyzed landscape elements (shape, colour, texture, scale) affect to the affinity of street furniture. chair which are included in rest facilities affect “texture”, “form”, “scale”, “color” in the order of preference of the molding design elements that influence landscape. Particularly, showed statistically significant on ‘colour’ element affecting the landscape preference than the other three elements. It means as the chair element which is rest facilities mainly affect on preferences, rather than texture, form, scale, colour. Monument in the landscape associated with a preference ‘colour’, ‘shape’, ‘texture’ ‘scale’ and appears to be in order of impact so we could get the consequence like chair and rest facilities show different aspects of the respectively. It means, visual element which are colour and shape significantly impact on landscape preferences. Third, information facilities such as signboard formative elements of landscape design preferences and correlation with negative showed that the correlation. That mean if the sign board is very negative influence on landscape preferences and the correlations of the design formative elements appear in order of ‘scale’, ‘colour’, ‘texture’. It also means that the ‘scale’ namely the size of advertising material and colour are adversely affected in terms of landscape. As these results, when design street furniture as the street scenery, facilities according to the kind of the shape element and need to focus on relative shape element according to the kind of facilities difference. Finally, so far as to clarify the street furniture, mainly ‘function’ and ‘system’ classification shows undesirable in outdoor scape. Thus, performed studies in relationship with landscape, classify ‘kind of facilities’ is more desirable than ‘system’.